Qualidade de dados fluviométricos obtidos através de perfilamento acústico - Vilanova, Mateus Ricardo Nogueira [UNESP]; Balestieri, José Antônio Perrella [UNESP] (FapUNIFESP (SciELO), 2013)
Acoustic Doppler current profilers are currently the main option for flow measurement and hydrodynamic monitoring of streams, replacing traditional methods. The spread of such equipment is mainly due to their operational advantages ranging from speed measurement to the greatest detail and amount of information generated about the hydrodynamics of hydrometric sections. As in the use of traditional methods and equipments, the use of acoustic Doppler profilers should be guided by the pursuit of data quality, since these are the basis for project and management of water resources constructions and systems. In this sense, the paper presents an analysis of measurement uncertainties of a hydrometric campaign held in Sapucaí River (Piranguinho-MG), using two different Doppler profilers - a Rio Grande ADCP 1200 kHz and a Qmetrix Qliner. 10 measurements were performed with each equipment consecutively, following the literature quality protocols, and later, a Type A uncertainty analysis (statistical analysis of several independent observations of the input under the same conditions). The measurements of the ADCP and Qliner presented, respectively, standard uncertainties of 0.679% and 0.508% compared with the averages. These results are satisfactory and acceptable when compared to references in the literature, indicating that the use of Doppler profilers is valid for expansion and upgrade of streamflow measurement networks and generation of hydrological data.
Quality analysis of streamflow data obtained by acoustic profiling
Keywords: Acoustic Doppler current profilers; Streamflow measurement; Uncertainty analyses